Language Evolution and Change Historical and Sociolinguistic Review - Jaizul W, Alim; Hadiaty Y, Siti (International Journal of Linguistics, Communication, and Broadcasting, 2024)
Language changes and developments, both nationally and internationally, are inevitable due to cultural acculturation and interactions between speakers of different languages. These changes can be internal, affecting the grammar system, or external, influenced by contact with other languages. Internal changes, which occur gradually, involve alterations in phonological systems, phrase order, and case and gender functions. External changes, resulting from interactions driven by economic, political, educational, and technological interests, can occur rapidly, often starting with lexical enrichment and extending to other language elements. This study examines the historical development and changes in two languages from the same family, German and English, to illustrate internal changes. Additionally, it explores the impact of external changes in multilingual societies, emphasizing the role of sociolinguistics in understanding the relationship between language and society. The methodology involves a qualitative approach, literature review, participant observation, and interviews to gather and analyze data descriptively. The study finds that internal language changes are driven by speaker behavior and innovation within communities, while external changes result from language contact and social interactions. These interactions lead to the introduction of loanwords, new morphological elements, phonemes, and speech variations. Examples from Indonesian, German, and English demonstrate how languages evolve due to these influences, creating new dialects and hybrid languages. The research highlights the importance of sociolinguistics in describing social status, improving social mobility through language use, and investigating dialect phenomena. The findings emphasize that language is a dynamic entity, constantly adapting to social, cultural, and technological changes, reflecting the diverse and evolving nature of human communication.